'Go with the flow ': A review of methods and advancements in blood flow imaging. Issue 3 (18th June 2012) - Daly, Susan M.; Leahy, Martin J.
Abstract Physics has delivered extraordinary developments in almost every facet of modern life. From the humble thermometer and stethoscope to X‐Ray, CT, MRI, ultrasound, PET and radiotherapy, our health has been transformed by these advances yielding both morphological and functional metrics. Recently high resolution label‐free imaging of the microcirculation at clinically relevant depths has become available in the research domain. In this paper, we present a comprehensive review on current imaging techniques, state‐of‐the‐art advancements and applications, and general perspectives on the prospects for these modalities in the clinical realm. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)